Relasi Guru PAI dan Harmonisasi Lingkungan Sekolah Berbasis Nilai Keberagaman - Fifi Risana; Nasor Nasor; Imam Syafe’I (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to analyze the role of Islamic Religious Education (PAI) teachers in fostering a harmonious and tolerant school environment based on religious values at SMK Negeri 1 Bakauheni. The research is grounded in the growing importance of promoting religious tolerance within Indonesia’s multicultural society, particularly in schools where students from diverse religious backgrounds interact daily. Employing a qualitative descriptive approach, this study explores in depth the experiences, perceptions, and social dynamics surrounding the internalization of tolerance values among students. Data were collected through in-depth interviews, participatory observations, and literature review. The findings reveal that PAI educators play a strategic role in integrating tolerance values into classroom learning by strengthening Islamic teachings on peace, justice, and respect for diversity. Teachers employ dialogical, integrative, and participatory methods to encourage students to understand and practice tolerance in real-life contexts. However, several challenges were identified, including differences in religious understanding, limited interfaith interaction, and the negative influence of social media, which can lead to intolerant attitudes. Furthermore, PAI teachers act as agents of change by providing moral exemplification, creating safe spaces for dialogue, and building an inclusive learning environment. The study emphasizes that the successful development of tolerance greatly depends on teacher competence, effective learning strategies, and school support through programs that promote humanistic and diversity-based values. Overall, this study concludes that a comprehensive, humanistic, and contextually relevant PAI implementation can effectively cultivate a culture of tolerance in schools.